Management failure as a mode of assessing corporate liability in the land public transport services sector. - Abd Razak, Adilah; Azmi, Ruzita (2012)

(untitled)
There are several risks associated with doing business through corporation. They include risk of noncompliance with legal requirement. Failure to manage compliance may result in the company’s prosecution for crime. Company’s liability for crime was and is still an interesting topic of legal debates. The outcomes of the discourse can be seen in volumes of papers discussing various corporate crime doctrines, and liability rules; statutory and judicial. In Malaysia corporate criminal liability is not an issue that is widely debated despite many instances where corporate activities had maimed individuals or caused loss of life. In view of the limited resources discussing corporate criminal liability rule in Malaysia, this study undertakes to review the current approach to assessing corporate criminal liability. The focus of the review is the common law approach and also statutory provisions. The center of the discussion is the latest legal development which incorporates management failure as a mode of assessing corporate liability for crime. This approach which is introduced through the Land Public Transport Act 2010 (LPTA 2010) and the Suruhanjaya Pengangkutan Awam Darat Act 2010 (SPAD 2010) allows the court to penalize the company for its management failure which may lead to safety and health risk to the public.